Identifikasi Coping Adiktif Warga Binaan Pemasyarakatan Menjelang Bebas melalui Pendekatan Rational Emotive Behavior Therapy (REBT) - Aiuningtyas Yuni Oetari; Wiryo Nuryono; Budi Purwoko; Evi Winingsih (IAI Miftahul Ulum Pamekasan, 2026)
Drug abuse is one of the focus of problems that is still urgent until now, the real impact of users is seen and felt not only biologically but also psychologically. The tendency to relapse or relapse in drug users is an obstacle in prevention and rehabilitation efforts for drug users. This study aims to help clients/counselees in finding new rational beliefs and identifying addictive coping patterns that can trigger relapse, repeating crimes, or recidivism in former drug users. The method used in this study is Qualitative with a Case Study model on the subjects of five Correctional Residents (WBP) aged 20-25 years in the final period of detention who are former drug users. Data collection techniques are carried out through observation, counseling interviews, and documentation. The approach used in therapy is Cognitive Behavioral Counseling with the Rational Emotive Behavior Therapy (REBT) approach. The main results of this study indicate the existence of irrational beliefs that trigger relapse tendencies such as; (1) Responsibility or burden of life after release, (2) Statements about easy access to narcotics, (3) Fear of negative judgment from society or those closest to them. The interconnectedness of these three factors forms an addictive coping pattern that emerges as a means of self-preservation to avoid anxiety before release. This study highlights addictive coping as a cognitive response to anxiety before release, which has not been widely studied in the context of the reintegration of narcotics inmates. The practical implications of this study include: (1) for counselors, understanding the client's cognitive and emotional state is crucial in eliminating irrational thought patterns and addictive coping as potential recidivism; (2) for school counselors, the finding that early exposure to narcotics during school confirms the need for early preventive intervention through the development of emotional regulation, rational thinking patterns, and skills in dealing with peers; (3) for the Development of the Guidance and Counseling Profession, the need for ongoing psychological support in preventing recidivism.